ANALISIS EKONOMI PENGGUNAAN CAMPURAN PUPUK ORGANIK FESES TERNAK SAPI PADA USAHATANI TOMAT(Lycopersicum esculentum Mill. L.) (Studi Kasus Di Desa Tondegesan Dua Kecamatan Kawangkoan Kabupaten Minahasa) - Pangajouw, Alvionita L; Wantasen, E; Lenzun, G. D.; Lumenta, I D.R (ZOOTEC, 2016)
ABSTRACT ECONOMIC ANALYSIS OF UTILIZATION OF MIX ORGANIC FERTILIZER FROM CATTLE FECES ON TOMATO (Lycopersicum esculentum Mill. L.) FARM (Case study at Tondegesan Two Village Kawangkoan District of Minahasa Regency) The objectives of this study were to analyze cost, income, production and factors affecting tomato farm using organic fertilizer from cattle feces at Tondegesan Two village, Kawangkoan district of Minahasa regency.        Respondents were defined by census method. Data were collected by interviewing mechanisms, direct observation and available documents. Data were based on primer data including land area, workers, salary, total seed, seed prize, total fertilizer applied, fertilizer price, tomato production per planting period, tomato selling price, production cost, income as well as general condition of farmer.  Secondary data were based on the reference (library and internet) or other institutions related with this study such as animal population and tomato farmers. Data were analyzed by different test using t test on pair samples. Results showed that costs of tomato farm using organic fertilizer from cattle feces were IDR 32,936,915 less than costs of tomato farm using non-organic fertilizer of IDR 38,659,431. On the other hand, farmer incomes using organic fertilizer from cattle feces were IDR 43,653,085 more than farmer income using non-organic fertilizer of IDR 34,938,069. The productions of tomato farm using organic fertilizer from cattle feces were 30,636 kg more than production of tomato farm using non-organic fertilizer of 29,439 kg. Using regression analysis of production function by cobb douglass method for factors affecting tomato farm indicated that the variables of workers and seed total affected significantly tomato production with probability of 0.005, while total organic and non-organic fertilizers did not affect tomato production. Therefore, it can be concluded that utilization of the organic fertilizer increased farmers’ income of the tomato farm.   Key words:Cattle feces organic fertilizer, tomato production, cost, income.